Influence of Private Tuitions on Quality of Secondary Education - Kaur, Kiranpreet; Singh, Kirandeep (RESEARCH REVIEW International Journal of Multidisciplinary, 2023)
The objective of the current study was to determine how private tuition affected the quality of secondary education. The primary aim of this study was to investigate the effects of private tutoring on secondary school students' academic performance, the motivations behind secondary school students enrolling in private tutoring, the gender distribution of secondary school students enrolled in private tutoring, and secondary school students' perceptions of the subjects' difficulty and importance. An exploratory, descriptive methodology was used in this investigation. The sample of 200 students from the government schools of Chandigarh was chosen using a random sampling technique. The researcher used a self-made tool on the effects of private tutoring to gather data. Wherever applicable, percentages were calculated to analyse the students' opinions. The survey's findings showed that the majority of students, whether they are receiving private instruction or not, find it challenging to study on their own. The majority of students claimed that individual tutoring improved their ability to comprehend their classes and perform well on exams. A study also showed that after paying tuition, a significant portion of students' academic performance increased. The results show that the majority of students believe that getting decent grades without tuition is quite difficult.